2019
DOI: 10.1038/s41598-019-40792-3
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification and phylogenetic classification of diverse bacterial pathogens in a multiplexed hybridization assay targeting ribosomal RNA

Abstract: Rapid bacterial identification remains a critical challenge in infectious disease diagnostics. We developed a novel molecular approach to detect and identify a wide diversity of bacterial pathogens in a single, simple assay, exploiting the conservation, abundance, and rich phylogenetic content of ribosomal RNA in a rapid fluorescent hybridization assay that requires no amplification or enzymology. Of 117 isolates from 64 species across 4 phyla, this assay identified bacteria with >89% accuracy at the species l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…These features present unique opportunities to leverage both the conserved regions for amplification across a broad panel of bacterial species as well as the unique regions to distinguish individual species. While the 16s ribosomal gene might seem ideal for this purpose and has indeed been used extensively for taxonomic classification (22 , 23 ), we found that it provided insufficient resolution to distinguish relevant bacterial pathogens. We, thus turned to a set of housekeeping genes present in most bacterial species ( 24 ).…”
Section: Introductionmentioning
confidence: 86%
“…These features present unique opportunities to leverage both the conserved regions for amplification across a broad panel of bacterial species as well as the unique regions to distinguish individual species. While the 16s ribosomal gene might seem ideal for this purpose and has indeed been used extensively for taxonomic classification (22 , 23 ), we found that it provided insufficient resolution to distinguish relevant bacterial pathogens. We, thus turned to a set of housekeeping genes present in most bacterial species ( 24 ).…”
Section: Introductionmentioning
confidence: 86%
“…We were unable to design probes predicted to specifically recognize the C. guilliermondii 28S subunit, or either subunit for C. dubliniensis , due to their similarity with other species (see Methods for details). However, we included these species in subsequent experiments, since our experience with bacterial species suggested that the overall probeset reactivity profile (PSRP) may still uniquely identify closely related species, even without a species-specific probe (18). In addition, we designed two genus-level “pan- Candida ” probes intended to recognize the 18S and 28S subunits from all Candida species while excluding non- Candida fungi.…”
Section: Resultsmentioning
confidence: 99%
“…Even with the advent of mass spectrometry-based pathogen identification, delays in clinical diagnosis often result from slow subculture steps required for optimal accuracy (5, 12). We recently developed Phirst-ID, a novel approach for amplification-free, multiplexed fluorescence-based rRNA hybridization to identify bacteria directly from clinical specimens (18). Here, we extend this Phirst-ID approach, designing a 21-plex probeset that can rapidly and accurately identify 11 common pathogenic Candida species from both isolated colonies (33/33 on a reference panel, 33/33 in an independent validation set) and positive clinical blood culture broths (concordant identification of 58/59 Candida species included in the reference panel, where the only discordant sample was a mixed specimen that included the species identified by Phirst-ID; no mis-identifications of 3 additional yeast species that were not in the reference panel).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 These features present unique opportunities to leverage both the conserved regions for amplification across a broad panel of bacterial species as well as the unique regions to distinguish individual species. While the 16s ribosomal gene might seem ideal for this purpose and has indeed been used extensively for taxonomic classification, 22,23 we found that it provided insufficient resolution to distinguish relevant bacterial pathogens. We thus turned to a set of housekeeping genes present in most bacterial species 24 .…”
Section: Introductionmentioning
confidence: 87%